Economic Analysis of Olive Oil Production Costs as Influenced by Farm Size in Syrian Coastal Region - Maitah, Mansoor; Å˜ezbovÃ¡, Helena; Murjan, Ahmed; Jehar, Mustofa (International Journal of Economics and Financial Issues, 2016)
To characterize the olive oil production costs and determine the optimal size of olive oil farm, a total of 130 farmers were interviewed in the region. The obtained data was subjected to regression analysis to formulate a mathematical model suitable for predicting the optimal farm size. Olive oil variable and fixed production costs for the five groups of farm sizes at Lattakia regions were calculated. Descriptive economic analysis indicated that the lowest average cost for producing 1 kg of olive oil was 676.9 SP and the highest one was 917.7SP. Also, the results indicated that the economically efficient farm size was 32.9 Dunum which represents only 29.1% of the current farm sizes in the region, therefore, decision makers should draw the land uses policies in their future plans, so that, to integrate land areas in such a way to approach the border of 32.9 Dunum. Keywords: Optimal farms size, olive oil, economic analyses, variable and fixed production costs. JEL Classifications: D24, D61, Q12